Acute vascular effects of the angiotensin II receptor antagonist olmesartan in normal subjects: relation to the renin-aldosterone system - L. M. Resnick; D. Catanzaro; J. E. Sealey; J. H. Laragh (Кардиоваскулярная терапия и профилактика)
The extent to which the clinical effects of angiotensin receptor blockers (ARB) are related to ambient renin system activity remains poorly defined. Therefore, we measured blood pressure (BP), large (C1) and small (C2) arterial compliance, systemic vascular resistance (SVR), plasma renin activity (PRA), and the 24-h urinary excretion of sodium (UNaV) and aldosterone before and 1, 2, 4, and 24 h after administration of single doses of placebo, and 5, 20, and 40 mg of the ARB olmesartan medoxomil to 12 unmedicated normotensive subjects. In the basal state, SVR was inversely related to UNaV (r=-0,3, p=0,04); the greater the UNaV, the more vasodilated the subject. Indices of arterial compliance, both C1 (r=-0,32, p=0,03) and C2 (r=-0,35, p=0,02) were inversely related to the basal PRA. Renin also predicted olmesartan-induced changes in C1 (r=0,43, p=0,004) and C2 r=0,33, p=0,04). The greater the basal PRA, the less the arterial compliance, and the more compliance improved after olmesartan. Both systolic (p=0,003) and diastolic (p<0,0001) BP fell significantly on olmesartan compared with placebo (MANOVA with time), and relations were observed between the basal PRA and olmesartan-induced changes in pressure (systolic BP: r=-0,414, p=0,012; diastolic BP: r=-0.561, p<0,0001) — the greater the initial PRA, the more olmesartan lowered BP. Furthermore, the more pressure fell, the more PRA rose reciprocally (r=-0,44, p=0,007). Finally, aldosterone excretion fell (sig=0,05) on each dose of olmesartan compared with placebo. We conclude that 1) the inverse relation of UNaV and SVR illustrates the reciprocal role of volume versus constrictor factors in maintaining normal BP; and 2) PRA is a physiologic determinant of arterial compliance in normal individuals and of the response to the ARB olmesartan. Measurement of PRA may help to predict clinical ARB responses in individual subjects.